Rancang Bangun Sistem Kendali Suhu pada Reaktor Torefaksi Menggunakan Mikrokontroler - Mareli Telaumbanua; Wahyu Hendi Setiawan; Agus Haryanto; Febryan Kusuma Wisnu; Winda Rahmawati; Budianto Lanya (Jurnal Ilmiah Rekayasa Pertanian dan Biosistem, 2024)
The increasing demand for energy causes a decrease in the availability of fossil fuels. Biomass from oil palm waste, namely empty oil palm bunches, can be used as an alternative fuel. The torrefaction process converts biomass into environmentally friendly biopellets with high added value. In this study, the calibration of the K-type thermocouple sensor was carried out using Arduino Uno and testing of the automatic pellet torrefaction tool from empty palm oil bunches. This study aims to develop an automatic control system for the pellet torrefaction tool. The design of the automatic torrefaction tool uses a microcontroller with a gas stove energy source. The dimensions of the support frame are the torrefaction tube (24 cm x 28 cm), the servo motor frame (15 cm x 9.5 cm) and the dynamo support frame (26 cm x 6.5 cm). The tool box is square (50 cm x 50 cm). The torrefaction tube has a volume of 2,826 cm3, a diameter of 15 cm and a height of 16 cm. The results showed that the system successfully reached a temperature of 300°C for 30 minutes from the initial temperature. The temperature accuracy test produced an average value of 92.12%. The stability of temperature control also proved to be quite good in achieving the specified setting point. The water content of torrefaction pellets at a temperature of 150-300°C was around 1-2%. The hydrophobicity of torrefaction pellets at a temperature of 250-300°C after being soaked for 24 hours had a clearer color and remained intact.